Integrated models for warehouse design and planning - Geraldes, Carla A.S. (2012)
Market competition requires continuous improvement in the design and operation of supply chains. Warehouse management is a field of interest for both practitioners and researchers and involves material, information and financial flow management in a highly dynamic environment. Designing and planning a warehouse (distribution centre) involve different levels of decision-making, with high levels of interactions and interdependencies. So, to ensure an efficient performance of the warehouse, decisions having a significant impact on each other must be integrated. The aim of this work is to develop integrated models capable of capture the complex tradeoffs of a warehouse system.